Canal Transportation and Centering Ability of ProTaper and SafeSider in Preparation of Curved Root Canals: A CBCT Evaluation - Delgoshayi, Negar; Abbasi, Mansoure; Bakhtiar, Hengameh; Sakhdari, Shirin; Ghannad, Setareh; Ellini, Mohammad Reza (Iranian Endodontic Journal, 2018)
Introduction: Maintaining the original central canal path is an important parameter in efficient root canal preparation. Instruments causing minimal changes in original canal path are preferred for this purpose. This study sought to compare canal transportation and centering ability of ProTaper and SafeSider instruments in curved mesiobuccal root canals of mandibular first molars using cone beam computed tomography (CBCT). Materials and Methods: In this experimental study, 30 mesiobuccal root canals of extracted human mandibular first molars with 20° to 40° curvature were randomly divided into two groups (n=15). After mounting in putty, preoperative CBCT scans were obtained of teeth. Root canals in group A were shaped using S1, S2, F1 and F2 of ProTaper system. Root canals in group B were instrumented to size 25 using SafeSider system according to the manufacturers’ instructions. Postoperative CBCT scans were then obtained. The distance between the external root surface and internal canal wall was measured at the mesial and distal at 1, 3 and 7 mm from the apex. The values measured on primary and secondary CBCT scans were compared to assess possible changes in original central canal path and canal transportation. Data were compared using the t-test and repeated measure ANOVA. Results: ProTaper and SafeSider were significantly different in terms of canal transportation and centering ability, and ProTaper was significantly superior to SafeSider in this respect (P<0.001). Conclusion: ProTaper (in contrast to SafeSider) is well capable of maintaining the original central canal path with the least amount of transportation. Keywords: Canal Transportation; Cone-beam Computed Tomography; ProTaper; Root Canal Preparation; SafeSider